Odpowiedź :
a) 9x+7=3x-11
9x - 3x = -11 - 7
6x = -18 / :6
x = -3
b) 2x+7=29-2x
2x + 2x = 29 - 7
4x = 22 / :4
x = 11/2 = 5 i 1/2
c) 3-7x=4x-19
-7x - 4x = -19 - 3
-11x = -22 / :-11
x = 2
d) 5x+7=3x+18
5x - 3x = 18 - 7
2x = 11 / :2
x = 11/2 = 5 i 1/2
e) 6x-15=3x-9
6x - 3x = -9 + 15
3x = 6 / : 3
x = 2
f) 2(x+6)=28-2x
2x + 12 = 28 - 2x
2x + 2x = 28 - 12
4x = 16 / :4
x = 4
g) 12x-7=3x+20
12x - 3x = 20 + 7
9x = 27 / :9
x = 3
h) 2(x+2)=5(x-1)
2x + 4 = 5x - 5
2x - 5x = -5-4
-3x = -9 / : -3
x = 3
i) 3x-2=11x+20
3x - 11x = 20 + 2
-8x = 22 / : -8
x = -11/4 = -2 i 3/4
Odpowiedź:
a)
9x + 7 = 3x - 11
9x - 3x = -11 - 7
6x = -18 /:6
x = -3
b)
2x + 7 = 4x - 19
2x - 4x = -19 - 7
-2x = -26 /:(-2)
x = -13
c)
3 - 7x = 4x - 19
-7x - 4x = -19 - 3
-11x = -22 /:(-11)
x = 2
d)
5x + 7 = 3x + 18
5x - 3x = 18 - 7
2x = 11 /:2
x = 11/2 = 5 1/2
e)
6x - 15 = 3x - 9
6x - 3x = -9 + 15
3x = 6 /:3
x = 2
f)
2(x + 6) = 28 - 2x
2x + 12 = 28 - 2x
2x + 2x = 28 - 12
4x = 16 /:4
x = 4
g)
12x - 7 = 3x + 20
12x - 3x = 20 + 7
9x = 27 /:9
x = 3
h)
2(x + 2) = 5(x - 1)
2x + 4 = 5x - 5
2x - 5x = -5 - 4
-3x = -9 /:(-3)
x = 3
i)
3) ?
3x - 2 = 11x + 20
3x - 11x = 20 + 2
-8x = 22 /:(-8)
x = -22/8 = -2 6/8 = -2 3/4
Szczegółowe wyjaśnienie: